Evaluation of incipient motion criteria for rock in Reno mattresses and rip rap - Stoffberg, Francis W. (Stellenbosch : University of Stellenbosch, 2008)
Thesis (MScEng (Civil Engineering))--University of Stellenbosch, 2005.